Agenda: Ormond Beach Task Force - California State Coastal Conservancy (California State Coastal Conservancy)
List of 7 topics to be covered in meeting such as volunteer opportunities at Ormond Beach, wetland/ land preservation status, and snowy plover & least tern recovery program.